The Importance of Melanocortin Receptors and Their Agonists in Pulmonary Disease - Moscowitz, Anna Elizabeth; Asif, Huda; Lindenmaier, Laurence Baily; Calzadilla, Andrew; Zhang, Chongxu; Mirsaeidi, Mehdi (Frontiers in Medicine, 2019)
Melanocortin agonists are ancient neuropeptides that have steroidogenesis and anti-inflammatory properties. They activate melanocortin receptors (MCR), a family of five seven-transmembrane G-protein coupled receptors. MC1R and MC3R are mainly involved in immunomodulatory effects. Adrenocorticotropin hormone (ACTH) and alpha-Melanocortin stimulating hormone (α-MSH) reduce proinflammatory cytokines in several pulmonary inflammatory disorders including asthma, sarcoidosis, and the acute respiratory distress syndrome. They have also been shown to reduce fibrogenesis in animal models with pulmonary fibrosis. By understanding the functions of MCR in macrophages, T-helper cell type 1, and T-helper cell type 17, we may uncover the mechanism of action of melanocortin agonists in sarcoidosis. Further translational and clinical research is needed to define the role of ACTH and α-MSH in pulmonary diseases.